Pengabdian Kepada Masyarakat Melalui Deteksi Dini Hipertensi Dan Diabetes Melitus Melalui Program Posbindu (Pos Pembinaan Terpadu) Di Desa Labuan Kabupaten Donggala - Maharani Chikita; Zamli Zamli (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Degenerative diseases are a group of chronic, noncommunicable diseases characterized by the deterioration of organ function due to the aging process. Hypertension, diabetes mellitus, and gout are three noncommunicable diseases with steadily rising prevalence in Indonesia. The lack of public awareness regarding the importance of routine health checkups is one of the main factors contributing to the high incidence of noncommunicable diseases in the community. This community service activity aims to detect hypertension, diabetes mellitus, and gout at an early stage through the Posbindu program in Labuan Village, Donggala Regency. The health screenings conducted included blood pressure measurements, blood glucose tests, uric acid tests, and anthropometric measurements (weight and height). A total of 53 participants took part in the activity, consisting of adults (ages 24–50) and older adults (ages 50–80). The results showed the highest uric acid levels among elderly women (64%), the highest blood pressure among elderly men (60% with hypertension), and the highest blood sugar levels among adult women (60% with high blood sugar). Following the health screenings and educational sessions, community members gained a better understanding of the importance of comprehensive health checkups even when healthy, as well as the importance of early detection of risks associated with not getting regular health checkups